2003
DOI: 10.1080/08941930390153032
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Aortic Coarctation Model for Studying Hypertension in the Pig

Abstract: We have developed a reproducible renovascular model of hypertension via a controllable, suprarenal aortic coarctation in the pig. This model has many potential applications, including investigation of the effects of acute hypertension in the conscious animal; identification of cardiac and vascular adaptations to chronic hypertension and their reversal; determining the effect of pharmacologic agents or other interventions on hypertension; and furthering our understanding of the implications of chronic hypertens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…Animal care in this study was approved by the University Animal Care Committee, Texas A&M University. Our porcine aortic coarctation model of hypertension was described previously (10). Briefly, inflatable silicone occluders (8 -12 mm, In Vivo Metrics; reinforced by Solomon Scientific) were surgically implanted around the aorta proximal to the diaphragm of Yucatan micro-miniswine (8 -11 mo).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Animal care in this study was approved by the University Animal Care Committee, Texas A&M University. Our porcine aortic coarctation model of hypertension was described previously (10). Briefly, inflatable silicone occluders (8 -12 mm, In Vivo Metrics; reinforced by Solomon Scientific) were surgically implanted around the aorta proximal to the diaphragm of Yucatan micro-miniswine (8 -11 mo).…”
Section: Methodsmentioning
confidence: 99%
“…Using the porcine aortic coarctation model presented (10), our laboratory recently showed that increased pro-collagen I synthesis, a known consequence of TGF-␤ activity, and increased smooth muscle proliferation occurred early in hypertension. In contrast, changes in contractile protein expression continued over an 8-wk period (13).…”
mentioning
confidence: 99%
“…Our aortic coarctation model for studying hypertension in the mini-pig is described elsewhere (Fossum et al 2003). Briefly, a balloon-expandable occluder is prefilled with a 50% dextrose solution, placed over a Gore-Tex soft tissue patch sheet, and secured with sutures around the aorta proximal to the diaphragm.…”
Section: Animal Modelmentioning
confidence: 99%
“…Renovascular hypertension was produced in pigs via suprarenal aortic coarctation as described in our previous study. 16 Briefly, hypertension was induced in 6 mature (8-to 11-month-old) male, micro-minipigs (Sinclair Research Center, Inc, Columbia, Mo) weighing between 21 and 37 kg. Systemic blood pressure of the animals was monitored by telemetry.…”
Section: Animal Modelmentioning
confidence: 99%